KUALITAS PELAYANAN BUS RAPID TRANS (BRT) KOTA SEMARANG - Wardani, Ellys Kusuma; Sundarso, Sundarso; Warsono, Hardi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Semarang is a city that has a dense population. The number of residents who live or occupy the city of Semarang make the problems that must be faced by the City of Semarang one of them is the problem of congestion. Based on data from the Central Bureau of Statistics of Semarang, Semarang number of motor vehicles until the year 2013 has increased, which consists of 11,111,071 1,572,652 motorcycles and four-wheeled vehicles. To minimize traffic congestion in the city of Semarang then made mass transport is Bus Rapid Trans (BRT), which until now has operated 4 koridor.Tujuan of this study was to analyze the quality of service Bus Rapid Trans (BRT) in Semarang based Theory by Zeithaml et al (1990) namely the quality of service can be measured from the 5 dimensions, namely: Tangible (Tangible), Reliability (reliability), Responsiveness (Responsiveness), Assurance (Guarantee), and empathy (Empathy) Data collection was conducted through field surveys and interviews from some of the informants related that BLU head BRT, passengers from the public and officers BRT, Based on the analysis and the results showed that the Quality Service Bus Rapid Trans (BRT) in the city of Semarang is less well characterized by a decrease in the number of passengers BRT in 2013, this indicates if people do not make the BRT as the main mode of transportation in the city of Semarang, based on the 5-dimensional indicator Parasuraman that of the 5 dimensions are 3-dimensional result is not good so it can be concluded that the quality of the ministry is still kurangbaik BRT is direct evidence dimensions (tangibles), Reliability (responsiveness) and empathy (Emphaty ), and these factors are becoming inhibitors, and the driver of the decline in the number of passengers BRT in 2013, the authors suggestion that the improvement and increase the number of shelters BRT, re-evaluation of the tariff system for BRT, socialize etiquette to people who can facilitate the purchase of tickets, and the scheduled departure and arrival BRT should be more flexibility so that people can more easily access under any circumstances.